The Role of Age on Beta-Amyloid1–42 Plasma Levels in Healthy Subjects - Zecca, Chiara; Pasculli, Giuseppe; Tortelli, Rosanna; Dell’Abate, Maria Teresa; Capozzo, Rosa; Barulli, Maria Rosaria; Barone, Roberta; Accogli, Miriam; Arima, Serena; Pollice, Alessio; Brescia, Vincenzo; Logroscino, Giancarlo (Frontiers in Aging Neuroscience, 2021)
Beta-amyloid (Aβ) plaques have been observed in the brain of healthy elderlies with frequencies strongly influenced by age. The aim of the study is to evaluate the role of age and other biochemical and hematological parameters on Aβ1-42 plasma levels in cognitively and neurologically normal individuals. Two-hundred and seventy five normal subjects stratified by age groups (<35 years, 35-65 years and >65 years) were included in the study. Aβ1-42 plasma levels significantly correlated with age (rs=0.27; p<0.0001) in the whole sample, inversely correlated with age in the first age group (rs=-0.25, p=0.01), positively correlated in the second group (rs=0.22, p=0.03), while there was no significant correlation in the older group (rs=0.02, p=0.86). Both age (β-estimate = 0.08; p < 0.001) and cholesterol (β-estimate = 0.03; p = 0.009) were significantly associated with Aβ1-42 plasma level in multivariable analysis. However, only the association with age survived post-hoc adjustment for multiple comparisons. The different effect of age on Aβ level across age groups should be explored in further studies to better understand the age-dependent variability. This could better define the value of plasma Aβ as biomarker of the Alzheimer neuropathology.